2009
DOI: 10.1172/jci39716
|View full text |Cite
|
Sign up to set email alerts
|

NSAIDs prevent, but do not reverse, neuronal cell cycle reentry in a mouse model of Alzheimer disease

Abstract: Ectopic cell cycle events (CCEs) mark vulnerable neuronal populations in human

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
94
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(96 citation statements)
references
References 61 publications
(89 reference statements)
2
94
0
Order By: Relevance
“…Furthermore, TREM2 overexpression in the brain of APPswe/PS1dE9 mice significantly attenuated neuronal and synaptic losses, which was accompanied by an improvement in spatial cognitive function. The neurotoxicity of Ab and proinflammatory cytokines led to the neuronal and synaptic damage in cellular and animal models of AD (Calkins and Reddy, 2011;Gouras et al, 2010;Kapadia and Sakic, 2011), which could be effectively prevented by Ab-targeting therapy or anti-inflammatory treatment (Adolfsson et al, 2012;Varvel et al, 2009). On consideration of this evidence, the attenuation of neuronal and synaptic losses by TREM2 overexpression was likely attributed to the amelioration of Ab neuropathology and neuroinflammation in this scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TREM2 overexpression in the brain of APPswe/PS1dE9 mice significantly attenuated neuronal and synaptic losses, which was accompanied by an improvement in spatial cognitive function. The neurotoxicity of Ab and proinflammatory cytokines led to the neuronal and synaptic damage in cellular and animal models of AD (Calkins and Reddy, 2011;Gouras et al, 2010;Kapadia and Sakic, 2011), which could be effectively prevented by Ab-targeting therapy or anti-inflammatory treatment (Adolfsson et al, 2012;Varvel et al, 2009). On consideration of this evidence, the attenuation of neuronal and synaptic losses by TREM2 overexpression was likely attributed to the amelioration of Ab neuropathology and neuroinflammation in this scenario.…”
Section: Discussionmentioning
confidence: 99%
“…Cite this article as Cold Spring Harb Perspect Biol 2015;7:a021287 sion associated with glial response and aberrant cell-cycle changes, as described in other brain regions (Yang et al 2001;Varvel et al 2009). …”
Section: Adult Neurogenesis In Neurodegenerative Diseasesmentioning
confidence: 99%
“…A role for inflammation in the pathogenesis of Alzheimer's disease (AD) is suggested by epidemiological studies that have reported a decreased incidence of AD in patients treated with nonsteroidal anti-inflammatory drugs (1,2); these findings are supported by evidence of preventative effects of these drugs in animal models of AD (3). Whereas the classical characteristics of AD are the presence of amyloid-b (Ab) plaques and neurofibrillary tangles, together with selective neuronal loss, there is also evidence of innate immune activation in AD, with activation of microglia, the primary resident immune cell of the CNS.…”
mentioning
confidence: 99%